DEVOLEPMENT OF PHYSICS LEARNING DEVICE BASED ON OUTBOUND FOR THE ACHIEVEMENT MASTERY OF MATTER AND ACHIEVEMENT MOTIVATION OF STUDENTS CLASS X MAN YOGYAKARTA II - Dyah Fitriana Saputri; Rahayu Dwisiwi Sri Retnowati (Jurnal Pendidikan Fisika, 2016)
This research is aimed to: (1) produce the physics learning device based on outbound which is feasible for the achievements mastery of matter and achievement motivation. (2) know the increasing category of mastery in physics matter of MAN Yogyakarta II students using physics learning device based on outbound. (3) know the category of achievements motivation of MAN Yogyakarta II students using physics learning device based on outbound. The method of this research is Research and Development with 4-D model. The research’s subject were the students of MAN Yogyakarta II class X MIPA 2 school year 2015/2016. Define stage, defined the learning device based on outbound in a circular motion for the increasing category of mastery in a circular motion matter and achievements motivation. Design stage designed the product of the physics learning device which is consist of RPP and LKPD. Develop stage, validated product by expert validator and practice validator. Disseminate stage, distributed physics learning device. The assessment about RPP and LKPD was got from expert validator. The increasing mastery of matter’s data was got from pretest and posttest. The achievement motivation’s data was collected from quessionnaire. The feasible of RPP was got from RPP observation’s sheet. The result of this research was a physics learning device based on outbound in a circular motion matter which is feasible for the learning in MAN Yogyakarta II. It was based on the validate’s result of expert validator and practice validator, that the average of RPP and LKPD based on outbound from all aspect in good category. The achievement mastery of matter students in high, enough, and low category consecutive 16 %, 52%, and 32%. Based on standart gain value, overall got 0.59, then it means the increasing category of students mastery was in enough category. The achievement motivation was in very good goodand enough category consecutive 24%, 56%, and 20%.Keywords: learning device based on outbound, mastery of matter, achievements motivation